2020
DOI: 10.21273/hortsci15134-20
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock and Plastic Mulch Effect on Watermelon Flowering and Fruit Maturity in a Verticillium dahliae–Infested Field

Abstract: Separately, grafting and the use of plastic mulch can increase yield, quality, and early harvest of watermelon (Citrullus lanatus), especially when plants are under biotic and/or abiotic stress. A 2-year field study was conducted to evaluate the combination of four different rootstocks and two types of plastic mulch (black and clear) on date of watermelon first flowering, fruit ripening, yield, and fruit quality when plants were exposed to Verticillium dahliae. Seedless watermelon cv. Secretariat was grafted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…"Crimson Sweet" watermelon grafted onto "Emphasis" and "Strongtoza" rootstocks grew more quickly and were more resistant to V. dahliae when compared to non-grafted plants (Buller et al, 2013). Devi et al (2020) found that Verticillium wilt severity differed between grafted watermelon plants and non-grafted 'Secretariat' watermelon plants. Grafted watermelon plants had 3.5 times less disease than non-grafted ones.…”
Section: Grafting Against Verticillium Wiltmentioning
confidence: 97%
“…"Crimson Sweet" watermelon grafted onto "Emphasis" and "Strongtoza" rootstocks grew more quickly and were more resistant to V. dahliae when compared to non-grafted plants (Buller et al, 2013). Devi et al (2020) found that Verticillium wilt severity differed between grafted watermelon plants and non-grafted 'Secretariat' watermelon plants. Grafted watermelon plants had 3.5 times less disease than non-grafted ones.…”
Section: Grafting Against Verticillium Wiltmentioning
confidence: 97%
“…Crimson Sweet was grafted onto rootstock cvs Mammoth, Calago, and Dako, compared to nongrafted (80%), when grown in soil artificially infested with an inoculum suspension of 10 6 conidia per ml. An additional study was conducted by Devi et al (2020) at Mount Vernon in the same field used by Attavar et al 2020 In five experiments over 4 years at Mount Vernon, WA, the AUDPC for watermelon grafted onto Tetsukabuto was always less than nongrafted plants, both grown with black plastic mulch ( Figure 4) (Attavar et al, 2020;Dabirian et al, 2017;Devi et al, 2020;Wimer et al, 2015b). When data from these four studies were analysed together, wilt generally was more severe on nongrafted Tri-X Palomar, the scion used in 2015, than on Sugar Baby or Secretariat, the scions used in 2014 or 2018-2019, respectively.…”
Section: G R Af Ting To Manag E Verti Cilli Um Wilt On Watermelonmentioning
confidence: 99%
“…The average total fruit weight was 9.4 kg per plant. Devi et al (2020) Super Shintosa (C. maxima Dotted and dashed lines show 95% confidence intervals for the grafted and nongrafted watermelon regression lines, respectively. The slope of the regression line for nongrafted plants increases with increasing density (p = .03), but the slope for grafted plants does not increase significantly with increasing density (p = .08).…”
Section: G R Af Ting To Manag E Verti Cilli Um Wilt On Watermelonmentioning
confidence: 99%
“…Studies on field production of grafted melons in a cool Mediterranean-type climate such as northwest Washington are limited to watermelon but not cantaloupe [34][35][36]. Rootstocks may have optimal soil temperature and moisture ranges and it is important to assess scion-rootstock combinations under the climatic and geographic conditions where the crop will be produced [31].…”
Section: Introductionmentioning
confidence: 99%